2022
DOI: 10.3390/s22103877
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Use of Surface-Enhanced Raman Scattering for Illicit Drug Detection

Abstract: The rapid increase in illicit drug use and its adverse health effects and socio-economic consequences have reached alarming proportions in recent years. Surface-enhanced Raman scattering (SERS) has emerged as a highly sensitive analytical tool for the detection of low dosages of drugs in liquid and solid samples. In the present article, we review the state-of-the-art use of SERS for chemical analysis of illicit drugs in aqueous and complex biological samples, including saliva, urine, and blood. We also include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 140 publications
(170 reference statements)
0
11
0
1
Order By: Relevance
“…[ 27,28 ] In fact, a recent review in 2022 was published that discussed current performance of various SERS substrates on various lab and portable Raman systems in the detection of illicit drugs in aqueous solution, saliva, urine, and plasma. [ 71 ] The limits of detection for various drugs were summarized and included cocaine (5 ppb), methamphetamine (17 ppm), MDMA (2.8 ppm), fentanyl (78 ppb), meperidine (741 ppb), and tramadol (131 ppm) as measured in aqueous solution, with PCP reported only in saliva at 1 ppm. Our experimentally determined LMC values shown in Table 3 for these drugs (cocaine [5 ppb], methamphetamine [500 ppb], MDMA [1 ppm], fentanyl [1 ppb], meperidine [250 ppb], tramadol [100 ppb], and PCP [10 ppb]) are comparable to or lower than these previously reported LODs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27,28 ] In fact, a recent review in 2022 was published that discussed current performance of various SERS substrates on various lab and portable Raman systems in the detection of illicit drugs in aqueous solution, saliva, urine, and plasma. [ 71 ] The limits of detection for various drugs were summarized and included cocaine (5 ppb), methamphetamine (17 ppm), MDMA (2.8 ppm), fentanyl (78 ppb), meperidine (741 ppb), and tramadol (131 ppm) as measured in aqueous solution, with PCP reported only in saliva at 1 ppm. Our experimentally determined LMC values shown in Table 3 for these drugs (cocaine [5 ppb], methamphetamine [500 ppb], MDMA [1 ppm], fentanyl [1 ppb], meperidine [250 ppb], tramadol [100 ppb], and PCP [10 ppb]) are comparable to or lower than these previously reported LODs.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the convenience of a portable instrument with the sensitivity of SERS enables the identification of on-site substances that may be found in small concentrations, as is often the case with many opioids. 208 Kimani et al showed that trace amounts of opioids can be detected in pharmaceutical tablets using hand-held SERS. 209 Smith et al devised a PLS model based on SERS spectra to quantify fentanyl and four of its analogs in concentrations up to 0.2 μM.…”
Section: ■ Chemistry: Seized Drugs and Toxicologymentioning
confidence: 99%
“…However, it also requires sample extraction and preparation, well-trained personnel, and advanced facilities (Harper et al, 2017), making this a challenging method to adopt for highthroughput WBE programs. Other detection techniques include gas chromatography-mass spectrometry (GC-MS), surface-enhanced Raman spectroscopy (SERS), lateral flow immunoassay, and carbon nanotube electrode, which efficiently detected illicit drugs in complex matrices (Angelini et al, 2019;De Rycke et al, 2020;Dragan et al, 2021;Azimi and Docoslis, 2022;Makanye et al, 2022). Recently, advances in sensor technology, specifically with aptamer sensors (aptasensors, Table 1) have shown promise as a new analytical tool that is selective, stable, automatic, and easy to use with low cost (Mao et al, 2020;Kumar et al, 2022).…”
Section: Detection and Analysis Of Drug Metabolites In Wastewatermentioning
confidence: 99%